(untitled) - Green, Emily K. (Minneapolis, MN, 2007)
Vegetables come in a variety of shapes and colors. They provide people with vitamin A, vitamin C, and fiber. Students will learn how many servings of vegetables they should have each day and how vegetables benefit their bodies.
Keywords: Nutrition,Dinh dưỡng,Rau quả trong dinh dưỡng con người,Vegetables in human nutrition